Probing for Dark Matter within Spiral Galaxy Disks - Kranz, T; Slyz, A; Rix, H (2001)
We explore the relative importance of the stellar mass density as compared to the inner dark halo, using the observed gas kinematics throughout the disk of the spiral galaxy NGC 4254 (Messier 99). We perform hydrodynamical simulations of the gas flow for a sequence of gravitational potentials in which we vary the stellar disk contribution to the total potential. This stellar portion of the potential was derived empirically from color corrected K-band photometry reflecting the spiral arms in the stellar mass, while the halo was modelled as an isothermal sphere. The simulated gas density and the gas velocity field are then compared to the observed stellar spiral arm morphology and to the H-alpha gas kinematics. We find that this method is a powerful tool to determine the corotation radius of the spiral pattern and that it can be used to place an upper limit on the mass of the stellar disk. For the case of the galaxy NGC 4254 we find R_cr = 7.5 +/- 1.1 kpc, or R_cr = 2.1 R_exp(K'). We also demonstrate that for a maximal disk the prominent spiral arms of the stellar component over-predict the non-circular gas motions unless an axisymmetric dark halo component contributes significantly (>~ 1/3) to the total potential inside 2.2 K-band exponential disk scale lengths.